Fatigue of fibre metal laminates - Chen, Jun Long (Nanyang Technological University, 2020)
This project studies the strength and stiffness degradation of different grades of GLARE with respect to cyclical loads. Four sets of GLARE were fabricated for the experiment using the autoclave machine. These specimens were put through tensile tests with cyclical loads of less than half of their Ultimate Tensile Strength. Material properties such as Young’s Modulus, Ultimate Tensile Strength, and stiffness were compared across the four sets of specimens. The results evaluate the better grade of GLARE with the strongest tensile properties to improve on its fatigue life.